The need to know: governing a region and its economy - Tennberg, Monica (fi=Lapin yliopisto, Arktinen keskus|en=University of Lapland, Arctic Centre|, 2015)
This paper investigates the ways in which the economy has been incorporated into the political reasoning and practice of region-building in the Barents Region among experts. While economic regionalism has been a key strand of studies on historic regionalism, this is not the case for the Barents Region. Yet, the natural resources of the region continue to raise high expectations about cross-border economic cooperation and development. Full appreciation of any regional development is underpinned by research and knowledge combining both political and economic considerations, but this basis is somewhat less solid in the Barents area. The knowledge base about the region and its development is therefore fragmented, limited and partial. This is an obvious problem, as many of the recent developments in the Barents Region, and also in the larger Arctic context, relate to economic opportunities, cooperation and development with implications also for political cooperation and governance. The paper analyses the development of political Barents studies from early 1990s until today, in particular its relation with economic developments in the region. publishedVersion